The Successful Implementation of Early Breastfeeding Initiation Judging From The Level Of Knowledge and Family Support At R.S Prasetya Husada Karangploso Malang - Mutmainah Mutmainah; Suci Anggraeni; Nur Yeny Hidajaturrokhmah (PT. Griya Eka Sejahtera, 2020)
Background: Early Initiation of Breastfeeding (EIB) is the process of letting the baby suckle on its own after birth. The baby is placed on the mother's chest and the baby himself with all his efforts to find a nipple to feed immediately. Method: The design of this study used an analytic observational method with a cross sectional approach. The number of respondents was 55 people. The instrument used is a questionnaire. The results of data analysis from statistics show that respondents have good knowledge of early breastfeeding initiation as many as 44 people (80%), which provide good support as many as 45 respondents' families (81.8%) and 50 respondents (90.9%) implemented early breastfeeding initiation). Results: the results of the chis-quare analysis between the knowledge variable and the success variable early breastfeeding initiation obtained p-value = 0.002. it means that there is a significant relationship between knowledge about early breastfeeding initiation and the success of implementing early breastfeeding initiation. the results of the chis-quare analysis between the family support variable and the success variable early breastfeeding initiation obtained p-value = 0.001. Conclusion: there is a significant relationship between family support with the successful implementation of early breastfeeding initiation. the existence of a relationship between knowledge, family support and the success of early breastfeeding initiation can be influenced by age status where the majority of the respondents are early adulthood and can also be influenced by the level of education where the education level of the respondents is high school is also influenced by the parity of the respondents where most of the respondents are multiple parity